PENGENALAN PUISI MELALUI GAMES MENYUSUN KATA MENGGUNAKAN LAGU ANAK DI KELAS 2 MI ISLAMIYAH SUROWONO - Sri Putrianingsih (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
ABSTRACT This practice aims to explore the effectiveness of introducing poetry through word-composing games using children's songs in class 2 of MI Islamiyah Surowono. The subjects in this practice were class 2 students at MI Islamiyah Surowono who were divided into several groups. The practical results show that the introduction of poetry through word-composing games using children's songs significantly increases students' interest and understanding of the elements of poetry. The implications of the results of this research can be the basis for a more innovative learning approach in teaching poetry to grade 2 children, especially at MI Islamiyah Surowono, by utilizing children's songs as an interesting and resourceful learning tool.